The evertree - Lu, Marie, 1984- (Spirit animals, 2015)
Conor, Abeke, Meilin, and Rollan have journeyed across Erdas, racing to stop a merciless foe. Now that journey is about to end. They must reach a place forgotten by time and face off against an ancient enemy breaking free from his prison. They have just one chance to stop him -- or the whole world will shatter.